ANALISIS PRODUKTIVITAS TENAGA KERJA DENGAN PENDEKATAN WORK SAMPLING DAN TIME STUDY PADA PROSES PRODUKSI SARUNG TANGAN DI CV. CAHAYA SETIA MULIA ABADI - Achmad Tazaki Al Mamtuh; Widya Setiafindari (Kampus Akademik Publiser, 2026)
Labor productivity is an important factor that affects the effectiveness and efficiency of production processes in manufacturing companies. At CV. Cahaya Setia Mulia Abadi, several non-productive activities were identified, such as waiting for materials, chatting, searching for work tools, using mobile phones, and being idle, which potentially reduce production performance. In addition, inefficient work movements were also found, causing wasted time and labor. This study aims to determine the level of labor productivity, analyze work activities using the work sampling and time study methods, provide improvement recommendations, and analyze work movements through motion study to develop a new Standard Operating Procedure (SOP) as an effort to improve work efficiency. The methods used in this research include work sampling to measure the proportion of productive and non-productive activities, time study to determine the standard production time, fishbone diagram and 5W+1H analysis to identify the root causes of inefficiency, and motion study to evaluate operator work movements. The results showed that the average production achievement reached 104.96% of the company’s target. Based on work sampling observations of 100 work activities, 88% were productive activities and 12% were non-productive activities. The time study results showed that the total standard time for the glove production process was 958.29 seconds or 15.97 minutes. The motion study analysis indicated that there were still several non-value-added movements, such as repeated tool retrieval and inefficient work transitions. Therefore, improvement proposals were made through simplification of work methods and the preparation of a new SOP to improve labor productivity and work efficiency sustainably. Keywords: Labor Productivity, Work Sampling, Time Study, Motion Study, SOP, Golf Gloves Production.